REMOVAL OF HEAVY METALS USING MAGNIFERA INDICA FROM DYEING EFFLUENT - Raj, I.R.Ifer; Udhayan, C. (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
Colour is the main attraction of any fabric. Manufacture and use of synthetic dyes from fabric dyeing as therefore become a massive industry today. Use of synthetic dyes has an adverse effect on all forms of life. Presence of sulphur naphthol, vat dyes, nitrates, acetic acids, soaps, enzymes, chromium compounds and heavy metals like copper, arsenic, lead, cadmium, mercury, nickel, and cobalt and certain auxiliary chemicals all collectively make the textile effluent highly toxic. It is important to remove these pollutants from the waste water before their final disposal. The study was performed to investigate the concentration of toxic heavy metals like cadmium (Cd) and Zinc (Zn). It was observed that the concentration of cadmium were much higher than the maximum permissible limits. Process parameters which include adsorbent dosages, PH and contact time of solution were varied in order to evaluate their influence on the adsorption process. The optimum contact time, dosage and PH for carbon with I.R-0.75 was 90 mins, 200mg and 7.00 with removal efficiency of 99.69%, 98.55% and 93.71% respectively. Hence easy and effective techniques are required for fine tuning of waste water treatment.